1986
DOI: 10.1002/ijc.2910380417
|View full text |Cite
|
Sign up to set email alerts
|

Seroepidemiologic survey of captive old‐world primates for antibodies to human and simian retroviruses, and isolation of a lentivirus from sooty mangabeys (Cercocebus atys)

Abstract: Sera from 526 Old-World monkeys and apes, representing 50 species and 20 genera and living in US zoos and vivaria, were screened for antibodies to HTLV-I, HTLV-III/LAV, and simian-AIDS retrovirus, type I (SRV-I). Sera were screened initially by ELISA, and ELISA-positive sera, as well as ELISA-negative sera from cage contacts, were further tested by Western blotting. A large number of false-positive and a small number of false-negative ELISA sera were identified. Although most true positive reactions were direc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
127
0
1

Year Published

1989
1989
2018
2018

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 221 publications
(131 citation statements)
references
References 37 publications
(27 reference statements)
3
127
0
1
Order By: Relevance
“…The natural hosts of SIV include many species of African monkeys and the chimpanzee (Pan troglodytes) (11,35,49,52). Prevalence of infection in various populations of captive and wild African primates may exceed 50% (11,49).…”
Section: Simian Immunodeficiency Virus (Siv)mentioning
confidence: 99%
See 2 more Smart Citations
“…The natural hosts of SIV include many species of African monkeys and the chimpanzee (Pan troglodytes) (11,35,49,52). Prevalence of infection in various populations of captive and wild African primates may exceed 50% (11,49).…”
Section: Simian Immunodeficiency Virus (Siv)mentioning
confidence: 99%
“…Prevalence of infection in various populations of captive and wild African primates may exceed 50% (11,49). Infection in these natural host species, however, is almost always subclinical (11,35). Asian macaques are susceptible to SIV infection, but naturally acquired (i.e.…”
Section: Simian Immunodeficiency Virus (Siv)mentioning
confidence: 99%
See 1 more Smart Citation
“…It is closely related, genetically and antigenically, to HIV-2. Limited serological surveys have shown no evidence that the virus occurs in nature in the Asian habitat of these animals (Lowenstein et al, 1986;Ohta et al, 1986). The first description of SIVmac was by investigators at the New England Primate Center in Massachusetts, who identified the lentivirus during studies on experimentally transmitted lymphomas of rhesus monkeys (Macaca mulatta) (Hunt et al, 1983).…”
Section: Sivmacmentioning
confidence: 99%
“…The first primate 1entivirus to be identified was SIV MAC at the New England Regional Primate Research Center following an outbreak of Iymphoma in rhesus (Macaca mulatta) and cynomoIgus macaques (Macacafascicularis) (Daniel et al, 1985). SIV MAC is not naturally found in Asian macaques (Macaca mulatta) (Lowenstine et al, 1986;Wu et al, 1991), but Its close reIationship to SIVsMM can be expIained by the introduction of SIV sMM-infected mangabeys into primate centres in the United States during the late 1960s and subsequent transfer of SIV into macaques. Each SIV appears to be endemic to the respective monkey species and none has yet been associated with disease in the natural host (Gardner et al, 1994).…”
Section: Viruses (Siv) Have Been Isoiated From African Green Monkeys mentioning
confidence: 99%